Predictive Potential of Flow Cytometry Crossmatching in Deceased Donor Kidney Transplant Recipients Subjected to Peritransplant Desensitization - Osickova, Klara; Hruba, Petra; Kabrtova, Katerina; Klema, Jiri; Maluskova, Jana; Slavcev, Antonij; Slatinska, Janka; Marada, Tomas; Böhmig, Georg A.; Viklicky, Ondrej (Frontiers in Medicine, 2021)
Recipient sensitization is a major risk factor of antibody-mediated rejection (ABMR) and inferior graft survival. The predictive effect of solid-phase human leukocyte antigen antibody testing and flow cytometry crossmatch (FCXM) in the era of peritransplant desensitization remains poorly understood. This observational retrospective single-center study with 108 donor-specific antibody (DSA)-positive deceased donor kidney allograft recipients who had undergone peritransplant desensitization aimed to analyze variables affecting graft outcome. ABMR rates were highest among patients with positive pretransplant FCXM vs. FCXM-negative (76 vs. 18.7%, p < 0.001) and with donor-specific antibody mean fluorescence intensity (DSA MFI) > 5,000 vs. <5,000 (54.5 vs. 28%, p = 0.01) despite desensitization. In univariable Cox regression, FCXM positivity, retransplantation, recipient gender, immunodominant DSA MFI, DSA number, and peak panel reactive antibodies were found to be associated with ABMR occurrence. In multivariable Cox regression adjusted for desensitization treatment (AUC = 0.810), only FCXM positivity (HR = 4.6, p = 0.001) and DSA number (HR = 1.47, p = 0.039) remained significant. In conclusion, our data suggest that pretransplant FCXM and DSA number, but not DSA MFI, are independent predictors of ABMR in patients who received peritransplant desensitization.